Analisis Pengaruh Inovasi Produk, Citra Merek, dan Strategi Digital Terhadap Keputusan Pembelian Konsumen Lab Milk Di Sukoharjo - Erni Widiastuti; Doni Mardiyanto (ITB AAS Indonesia Surakarta, 2024)
In this research, the author aims to determine the influence of product innovation, brand image and digital strategy on the purchasing decisions of Lab Milk consumers in Sukoharjo. The research method used is a quantitative research method using primary data and secondary data. The population used in this research is Lab Milk consumers in Sukoharjo whose number cannot be known with certainty. Because the population size is unknown, the number of respondents in this study was determined using the Paul Leedy formula and the number of respondents was 100 people. The sampling technique is using random sampling technique. The data collection method used in this research is by distributing questionnaires to respondents taken as samples. The data analysis techniques used in this research are instrument tests, multiple linear regression tests, t tests, F tests and coefficient of determination tests. The results of data analysis in this research can be concluded that product innovation, brand image and digital strategy have a significant influence on the purchasing decisions of Lab Milk consumers in Sukoharjo. Keywords : product innovation, brand image, digital strategy, and purchasing decisions